Sub-femtogram simultaneous elemental detection in multicomponent nanomatrices using laser-induced plasma emission spectroscopy within atmospheric pressure optical traps. - Purohit, Pablo; Fortes-Román, Francisco Javier; Laserna-Vázquez, José Javier (American Chemical Society, 2019)
Simultaneous detection of multiple constituents in the characterization of state-of-the-art nanomaterials is an elusive topic to a majority of the analytical techniques covering the field of nanotechnology. Optical catapulting (OC) and optical trapping (OT) have recently been combined with laser-induced breakdown spectroscopy (LIBS) to provide single nanoparticle resolution and attogram detection power. In the present work, the multielemental capabilities of this approach are demonstrated by subjecting two different types of nanometric ferrite particles to LIBS analysis. Up to three metallic elements in attogram quantities are consistently detected within single laser events. Individual excitation efficiency for each species is quantified from particle spectra showing an exponential correlation between photon production and the energy of the upper level of the monitored atomic line. Moreover, a new sampling strategy based in skimmer-like 3D printed cones which allows for thin dry nanoparticle aerosols to be formed via optical catapulting is introduced. Enhanced sampling resulted in an increase of the sampling throughput by facilitating stable atmospheric-pressure optical trapping of individual particles and spectroscopic chemical characterization within a short time frame
Keywords: Espectroscopía de plasma inducido por láser; Nanopartículas; LIBS; Single nanoparticle analysis; Multielemental analysis